Extended Agrarian Question in Concessionary Capitalism: The Jakarta's Kaum Miskin Kota. (August 2022) - Batubara, Bosman; Rachman, Noer Fauzi
This article reassesses agrarian questions by using the ongoing explosion in urban and urbanization theories to explain Jakarta's urban poor (the Kaum Miskin Kota ) as an extended agrarian question. It shows how the two capitalist development trajectories identified by Lenin as the Russian and American paths, or the transformation of feudal large-scale and small landholders into capitalists, respectively, do not apply in Indonesia. In the latter, a "concessionary capitalism" of large-scale land claims and allocations by the state is observed. This specific process produces specific agrarian questions of soil/land and labor through which the urban poor germinated. It closes with a political project, that is, to open more alliance-building possibilities between urban and rural social movements.